New treatment options for metastatic renal cell carcinoma with prior anti-angiogenesis therapy. Issue 1 (December 2017) - Zarrabi, Kevin; Fang, Chunhui; Wu, Shenhong
Abstract Angiogenesis is a critical process in the progression of advanced renal cell carcinoma. Agents targeting angiogenesis have played a primary role in the treatment of metastatic renal cell carcinoma. However, resistance to anti-angiogenesis therapy almost always occurs, and major progress has been made in understanding its underlying molecular mechanism. Axitinib and everolimus have been used extensively in patients whom have had disease progression after prior anti-angiogenesis therapy. Recently, several new agents have been shown to improve overall survival in comparison with everolimus. This review provides an in-depth summary of drugs employable in the clinical setting, the rationale to their use, and the studies conducted leading to their approval for use and provides perspective on the paradigm shift in the treatment of renal cell carcinoma. Highlighted are the newly approved agents cabozantinib, nivolumab, and lenvatinib for advanced renal cell carcinoma patients treated with prior anti-angiogenesis therapy.